Understanding the Potential of Using EdTech to Measure and Mitigate Learning Losses in Latin America and the Caribbean - Wyss, Natalie; Myers, Christina (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and the Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in December 2021. The UNICEF team requested a resource that summarises what is known about the use of technology and other approaches to measure and mitigate learning losses related to Covid-19 impacts on education in the LAC region. This resource aims to support UNICEF country offices and partners in the LAC region to assess learning losses and inform school reopening and the development of hybrid education strategies. Our research found that there are limited EdTech approaches to measuring and mitigating learning losses, and fewer still that are specific to the LAC region. This piece outlines the following: What is understood about learning losses and how they can be quantified; What common guidance and evidence suggest are the most effective ways to mitigate Covid-19-specific learning losses; How established EdTech tools and non-tech-based approaches can be leveraged and applied to both processes. Keywords: learning losses; school reopening; personalised learning; assessment; remedial education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech for Learners With Cognitive and Learning Disabilities: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Afzal, Nimra (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with cognitive and learning disabilities. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. We discuss the nature of EdTech for learners living with cognitive and learning disabilities, the effectiveness of these initiatives, and barriers for accessing EdTech. The RER aims neither to advocate nor discourage the use of technology to support education for learners with coginitive and learning disabilities, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; cognitive disabilities; learning disabilities; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; ⛔ No INSPIRE recid found

SWOT Analysis of the Kenya Education Cloud - Groeneveld, Caspar; Kimenyi, Eric; Kaye, Tom (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _cover:v3; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode